Trace elemental fingerprinting of shells and soft tissues can identify the time of blue mussel (Mytilus edulis) harvesting. (March 2021) - Bennion, Matthew; Morrison, Liam; Shelley, Roseanne; Graham, Conor
Abstract: Reliance on seafood for a source of animal protein is growing globally and this is likely to continue as Earth's population continues to rise. An active shift towards farmed produce over wild caught is occurring, attributed to dwindling wild populations, increased productivity potential and increased food security needs. Although production is rising, producers and regulators are continually challenged as passive filter feeding shellfish such as mussels are impacted by disease outbreaks, toxic algae blooms, pollution and food fraud that pose a risk to the market. This risk can manifest as mortality events and loss of stock, but also via consumer safety and subsequent loss of trust. To combat this threat, accurate and reliable traceability tools are necessary to give regulators power to maintain consumer safety and subsequently, trust. Recent research has demonstrated that trace element fingerprints (TEFs) based on the shell and soft tissues can identify the site of harvest of blue mussels ( Mytilus edulis) (Bennion et al., 2019. Trace element fingerprinting of blue mussel ( Mytilus edulis ) shells and soft tissues successfully reveals harvesting locations. Science of The Total Environment, 685, 50–58) and king scallops ( Pecten maximus) (Morrison et al., 2019. Spatio-temporal trace element fingerprinting of king scallops ( Pecten maximus ) reveals harvesting period and location. Science of The Total Environment, 697, 134121) with 100% success. Here, we test the temporal stability of trace element fingerprints (TEFs) of blue mussels within the aquaculture sphere, over five harvesting dates spanning two years. Computational models constructed using the trace element signatures of shells and soft tissues show near absolute temporal differences of TEFs between harvesting dates. However, TEFs based on a combination of both the shell and periostracum of mussels enabled 96% of all individuals to be correctly assigned to their date of harvest indicating that this method can not only identify the location but also the date of harvest of bivalve shellfish. This technique offers a reliable scientific-based traceability tool for regulators to uphold food safety standards and can prove an invaluable asset within the seafood regulatory arsenal. Highlights: TEFs of blue mussel shells and soft tissues varied over time. A combination of structures analysed increased classification success. TEFs could distinguish between harvesting dates with 96% success rate. TEF can identify the time of harvest of bivalve shellfish. A powerful tool for industry regulators to trace bivalve produce is provided.